2021
DOI: 10.1038/s41598-021-98613-5
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of computed tomography-measured psoas muscle thickness per height for predicting mortality in patients undergoing hemodialysis

Abstract: Computed tomography (CT)-measured psoas muscle thickness standardized for height (PMTH) has emerged as a promising predictor of mortality. The study aimed to investigate whether PMTH could accurately predict mortality in patients undergoing hemodialysis. We examined 207 patients (mean age: 63.1 years; men: 66.2%) undergoing hemodialysis for more than 6 months in hospital affiliated clinic. PMTH was calculated at the L3 vertebra level using CT. Patients were divided according to the PMTH cut-off points: 8.44 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 41 publications
2
10
0
Order By: Relevance
“…PMI was positively and independently associated with male sex and GNRI. Previous studies have reported that muscle mass volume differed with sex 6 , 14 , 17 , 18 ; in this study, the PMI was significantly higher in men than in women. In patients undergoing hemodialysis, PEW is highly prevalent and is associated with increased risks of morbidity and mortality 3 6 .…”
Section: Discussionsupporting
confidence: 44%
See 3 more Smart Citations
“…PMI was positively and independently associated with male sex and GNRI. Previous studies have reported that muscle mass volume differed with sex 6 , 14 , 17 , 18 ; in this study, the PMI was significantly higher in men than in women. In patients undergoing hemodialysis, PEW is highly prevalent and is associated with increased risks of morbidity and mortality 3 6 .…”
Section: Discussionsupporting
confidence: 44%
“…Previous studies have reported that muscle mass volume differed with sex 6 , 14 , 17 , 18 ; in this study, the PMI was significantly higher in men than in women. In patients undergoing hemodialysis, PEW is highly prevalent and is associated with increased risks of morbidity and mortality 3 6 . GNRI, which is easily calculable based on the serum albumin level and BMI, is a useful nutritional indicator to stratify the risk of PEW 22 26 ; therefore, our results suggest that PMI may be an indicator of PEW.…”
Section: Discussionsupporting
confidence: 44%
See 2 more Smart Citations
“…PEW, a malnutritional state defined by a loss of fat and muscle mass because of catabolic inflammation, is prevalent in patients receiving HD and is also related to increased risks of mortality [4,[21][22][23][24]. The MIS proposed by Kalanter-Zadeh et al is the gold standard method for assessing the nutritional status of HD patients [2].…”
Section: Discussionmentioning
confidence: 99%